(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: The ketogenic diet (KD) is a cheap and effective alternative therapy for most epilepsy. There are paucity of experimental data in Nigeria on the usefulness of KD in epilepsy models. This is likely to be responsible for the poor clinical acceptability of the diet in the country. This study therefore aimed at providing experimental data on usefulness of KD on seizure models. The study used 64 Wistar rats that were divided into two dietary groups [normal diet (ND) and ketogenic diet (KD)]. Animal in each group were fed for 35days. Medium chain triglyceride ketogenic diet (MCT-KD) was used and it consisted of 15% carbohydrate in normal rat chow long with 5ml sunflower oil (25% (v/w). The normal diet was the usual rat chow. Seizures were induced with one of Pentelyntetrazole (PTZ), 4-Aminopyridine (AP) and Strychnine (STR). Fasting glucose, ketosis level and serum chemistry were determined and seizure parameters recorded. Serum ketosis was significantly higher in MCT-KD-fed rats (12.7 ±2.6) than ND-fed (5.17±0.86) rats [p=0.003]. Fasting blood glucose was higher in ND-fed rats (5.3±0.9mMol/l) than in MCT-KD fed rats (5.1±0.5mMol/l) with p=0.9. Seizure latency was significantly prolonged in ND-fed compared with MCT-KD fed rats after PTZ-induced seizures (61±9sec vs 570±34sec) and AP-induced seizures (49±11sec vs 483±41sec) p<0.05. The difference after Str-induced seizure (51±7 vs 62±8 sec) was not significant (p>0.05). The differences in seizure duration between ND-fed and MCT-KD fed rats with PTZ (4296±77sec vs 366±46sec) and with AP (5238±102sec vs 480±67sec) were significant (p<0.05), but not with STR (3841±94sec vs 3510±89sec) [p>0.05] respectively. The mean serum Na+ was significantly higher in MCT-KD fed (141.7±2.1mMol/l) than ND-fed rats (137±2.3mMol/l) with p<0.05. There was no significant difference in mean values of other serum electrolytes between the MCT-KD fed and ND-fed animals. MCT-KD caused increase resistance to PTZ-and AP-induced seizures, but has no effect on STR-induced seizures. This antiseizure property is probably mediated through GABAergic receptors (PTZ effect) and blockade of membrane bound KATP channels (AP effect) with some enhancement by serum ketosis.